Um Estudo da evolução da GQT por meio do modelo de resposta gradual da teoria da resposta ao item - Oliveira, Kátia Michelle Matos de (2010)
Aiming to evaluate the degree of maturity in the use of tools and techniques of Total Quality Management (TQM), and its evolution over the past 10 years, in the companies of transformation and construction of medium and large scale in the State of Ceara, this study used the Graded Response Model of Item Response Theory (IRT). This model was designed to examine responses graded and capable of ordinate. As a basis of comparison for possible evaluates in the maturity, it was used the work done by Alexander in 1999. The methodology used for collecting data was the quantitative survey, using a structured questionnaire in Likert scale with five response categories. The study used a model for assessment of maturity by creating a standardized measurement scale with the support of the IRT, whereby it became possible to compare and to check that there was a low evolution of maturity of organizations, especially taking into account the importance of quality as a competitive differential for maintenance companies in the global market. The scale constructed may serve as a basis to enable companies to identify potential practice has not implanted, allows, still monitoring their development level of maturity